Unscrambling of Respiratory Rehabilitation Guidance for COVID-19, Discharged Chapter (Second Edition) - Jiaxi WANG; Xin WANG; Xuanming SITU; Xi LU; Mingzhen LI; Laiyong HOU; Yuxiao XIE (康复学报)
We introduce the chapter for discharged patients in"Guidelines for the respiratory rehabilitation of the Corona Virus Disease 2019(the second edition)"in this paper and present with video. The purposes are to help respiratory doctors, rehabilitation doctors, general physicians, rehabilitation therapists, physiotherapists, occupational therapists, nurses and other medical professionals to perform professional respiratory rehabilitation for the discharged patients with COVID-19. The contents of respiratory rehabilitation mainly include the following:①Breathing training; ②Inspiratory muscles training; ③Sputum excretion training; ④Aerobic training; ⑤Activity ability training in daily life; ⑥Strength training; ⑦Balance function training. The breathing training and the inspiratory muscles training could help the patients to improve respiratory efficiency, reduce consumption of breathing, and relieve symptoms of dyspnea. The Sputum excretion training could help the patients to reduce sputum retention and risk of infection. The aerobic training could help the patients to improve physical fitness. The strength training and balance function training could help the patients to improve their limb motor function. Activity ability training in daily life could help the patients to return to family and return to work. Aspects are all introduced in detail both in the paper and in the video such as when to begin the training, what are the indicators to stop, the standard procedures, the specific form, intensity, time, frequency, points for attention when training.